Evaluation of Methods to Build a Community of Learners on the Learning Advisory System in an Online Training Environment - Bui Xuan , Huy; Nguyen An , Te; Tran Thi Song , Minh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Online training is growing strongly but it also makes learners easily lost and disoriented in a large virtual learning environment because there are no instructors and no specific classmates. As a result, the learner's motivation to learn is reduced. Therefore, there is a need to develop a recommender systems to solve the problem of information overload making it easy for learners to accurately and timely access the resources and services they are interested in. The principle of the learning recommender system is based on a community of learners with similar characteristics and good learning outcomes to give appropriate advice to a particular learner on decision-making issues such as: choosing learning methods, learning resources, study groups, and registering for subjects. The degree of precision in building a community of learners will affect the quality of advice. The content of this paper will present the methods of building a learner community on the learning recommend system in the online training environment as well as the issue of evaluating the effectiveness of the methods.
Keywords: E-Learning; Recommend System; Learner profile; Learner community